Auditoría tributaria a la empresa total car Solution de la ciudad de Riobamba para disminuir el riesgo tributario del periodo 2015 - Bonilla Erazo, Paulina Dolores (2017)
TAX AUDIT TO TOTAL CAR SOLUTION ENTERPRISE OF RIOBAMBA CITY TO DECREASE THE TAX RISK FOR THE PERIOD OF 2015 ABSTRACT: The present research project includes the execution of a TAX AUDIT TO TOTAL CAR SOLUTION OF RIOBAMBA CITY FOR THE PERIOD OF 2015. The objective is to identify the levels of taxation risk for this company. The content of this work is distributed in five chapters as follow: CHAPTER I. Referential Framework.- it contains general aspects of a scientific research: the problem of investigation, incidence factors, research guidelines, objectives and justification of the need to carry out the project, in other words, the cientific contribution to the profession through the inclusion of the knowledge CHAPTER II. Theoretical Framework.- It is separated into units of study. The first unit contains Generalities of the company, an overview of the company through its history, mission, vision, objectives, position and market strategies, as well as an analysis of factors and company risks. The second unit contains the development of new theoretical knowledge from the existing knowledge in the areas of Auditing and Tax Auditing; following, the third unit contains an analysis of the legislation applicable to this case of study; it concludes with a fourth unit of tax management. CHAPTER III. Methodological Framework.- This chapter includes information about the methodology used in the research, and the actual development of the research that starts from the hypothesis and ends with the verification of it. This chapter is important for understanding the main information of the auditing process that, as we shall see, contains the stages of planning, execution and communication of results. CHAPTER IV. Conclusions and Recommendations.- Substantive information on an audit process is summarized in the findings, which are included in this chapter as conclusions and recommendations. CHAPTER V. Proposal.- As the last chapter of the project, an specific action plan is presented for the company studied, in a certain way transferable to companies of similar comercial, economic and taxation activity